Marian Maciejewski – przeoczone - Łukaszuk, Małgorzata (Colloquia Litteraria, 2014)
Marian Maciejewski – the overlooked This short piece summarises in a synthetic way professor Marian Maciejewski’s ‘personal research interests’ and his own ‘methodological standing’. Methodology was a real cognitive and axiological issue for him, hence the choice of kerygmatic reading of text turned out to be fundamental in his works; one that set the canon of writings to be subjected to a holistic and extremely responsible interpretation. Maciejewski focused his attention on testimonies of troubled and bruised existence of ‘the sin’s shame’. He looked upon masterpieces, reading them closely, critically and with great intensity. Maciejewski took creative awareness (especially romantic one) and formulated a strong synthesis of demands and realisations in such a way that the language of discourse was revised. This language is nowadays used not only to talk about the very phenomena Maciejewski was concerned with.